Sociodemographic disparities in the utilization of proton therapy for prostate cancer at an urban academic center - Kristina D. Woodhouse, MD; Wei-Ting Hwang, PhD; Neha Vapiwala, MD; Akansha Jain; Xingmei Wang, MS; Stefan Both, PhD; Meera Shah, BS; Marquise Frazier, RT(T), MBA; Peter Gabriel, MD; John P. Christodouleas, MD, MPH; Zelig Tochner, MD; Curtiland Deville, MD (Advances in Radiation Oncology, 2017)
Purpose: Despite increasing use, proton therapy (PT) remains a relatively limited resource. The purpose of this study was to assess clinical and demographic differences in PT use for prostate cancer compared to intensity modulated radiation therapy (IMRT) at a single institution. Methods and materials: All patients with low- and intermediate-risk prostate cancer (N = 633) who underwent definitive radiation therapy between 2010 and 2015 were divided into PT (n = 508) and IMRT (n = 125) comparison groups and compared using χ2 and independent sample t tests. Univariable and multivariable logistic regression analyses were conducted to assess the associations between PT use and demographic, clinical, and treatment characteristics. Results: The PT and IMRT cohorts varied by age, race, poverty, distance, treatment year, and treating physician. Patients who underwent IMRT were more likely to be older (mean age, 66 vs. 68 years), black (51% vs. 75%), and living in poverty or close to the facility (mean distance between residence and facility, 90 vs. 21 miles; P < .05). Prostate-specific antigen, prostate volume, and International Index of Erectile Function were significantly higher in the IMRT cohort (P < .05), but insurance type, risk group, tumor stage, Gleason score, and patient-reported urinary and bowel scores did not differ significantly (P > .05). Patients who underwent PT were more likely to receive hypofractionated therapy and less likely to receive androgen deprivation therapy (P < .01). On multivariable analysis, black (odds ratio [OR], 0.29; 95% confidence interval [CI], 0.15-0.57) and other race (OR, 0.42; 95% CI, 0.20-0.90); distance (OR, 1.14; 95% CI, 1.06-1.24); treatment years 2011 (OR, 4.87; 95% CI, 2.23-10.6), 2012 (OR, 8.27; 95% CI, 3.43-19.9), and 2014 (OR, 4.44; 95% CI, 1.94-10.2) relative to 2010; and a single treating physician (OR, 0.38; 95% CI, 0.18-0.81) relative to the reference physician with the highest rate of use were associated with PT use, whereas clinical factors such as prostate-specific antigen, prostate volume, International Index of Erectile Function, and androgen deprivation therapy were not. Conclusion: Sociodemographic disparities exist in PT use for prostate cancer at an urban academic institution. Further investigation of potential barriers to access is warranted to ensure equitable distribution across all demographic groups.